Male Assistance in Parental Care Does Not Buffer Against Detrimental Effects of Maternal Inbreeding on Offspring - Ratz, Tom; Castel, Elise; Smiseth, Per T. (Frontiers in Ecology and Evolution, 2018)
The severity of inbreeding depression often varies across environments and recent work suggests that social interactions can aggravate or reduce inbreeding depression. For example, stressful interactions such as competition can exacerbate inbreeding depression, whereas benign interactions such as parental care can buffer against inbreeding depression in offspring. Here, we test whether male assistance in parental care can buffer against the detrimental effects of maternal inbreeding on offspring fitness in the burying beetle Nicrophorus vespilloides. Our results confirm that maternal inbreeding had detrimental effects on offspring survival. However, we found no evidence that male assistance in parental care buffered against those effects on offspring fitness. Outbred females benefitted from male assistance, gaining more weight over the breeding attempt when assisted by a male. In contrast, inbred females did not benefit from male assistance, gaining as much weight regardless of whether they were assisted by a male or not. Surprisingly, we find that males gained more weight during the breeding attempt when mated to an inbred female, suggesting that males benefitted from assisting an inbred female partner in terms of their weight gain. Overall, our findings suggest that parental care or other benign social interactions may not always buffer against detrimental effects of inbreeding depression.